2015
DOI: 10.1007/978-3-319-20609-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the Development of Computational Thinking: A Robotic Platform Controlled by Smartphone

Abstract: The difficulty of students in learning logic and programming languages leads the research of technological solutions to assist in the teaching-learning process. Among these solutions, two common approaches are robotics and graphical-based programming languages. Researches indicate that these tools can aid learners to think systematically and develop computational thinking. Therefore, this work proposes the Coffee Platform, which is composed by a Web-based block programming environment and a smartphone as a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…Many researchers have shown that students can process information faster when using ER; likewise, ER activities are usually well accepted by boys and girls. Furthermore, they feel interested and motivated to continue learning ER topics compared to other disciplines (Witherspoon et al, 2016); allowing to reach a broad audience since robots typically stimulate the interests of students (Catlin & Woollard, 2014), comprising the entire range of motivation components (attention, relevance, confidence, attitude, and satisfaction) (Sarmento et al, 2015). Also, to capture students' attention, ER integrates several areas, such as Programming, Mathematics, Mechanics, and Electronics, for instance.…”
Section: Educational Roboticsmentioning
confidence: 99%
“…Many researchers have shown that students can process information faster when using ER; likewise, ER activities are usually well accepted by boys and girls. Furthermore, they feel interested and motivated to continue learning ER topics compared to other disciplines (Witherspoon et al, 2016); allowing to reach a broad audience since robots typically stimulate the interests of students (Catlin & Woollard, 2014), comprising the entire range of motivation components (attention, relevance, confidence, attitude, and satisfaction) (Sarmento et al, 2015). Also, to capture students' attention, ER integrates several areas, such as Programming, Mathematics, Mechanics, and Electronics, for instance.…”
Section: Educational Roboticsmentioning
confidence: 99%
“…UNC++Duino [18] BlocklyDuino Program robots to teach CS concepts. The Coffee Platform [131] Blockly Support computational thinking skills through robotics. LearnBlock [12] -Robot-agnostic educational tool.…”
Section: Name Metatool Topicmentioning
confidence: 99%
“…Sáez-López et al (2016), muestran los resultados favorables de enseñar conceptos de computación en los primeros años escolares debido a la motivación que causa el entorno Scratch, para muchos profesores es una herramienta nueva y representa un reto aprender a usarlo e integrarlo en el aula, pero altamente justificable el esfuerzo debido a la aceptación de los niños, considerando que para ellos también es reto a vencer (Sentance & Csizmadia, 2017;Wong, Cheung, Ching, & Huen, 2015;Saari, Blanchfield, & Hopkins, 2016;Byrne, Fisher, & Tangney, 2015;Zeng, 2015;Bustillo & Garaizar, 2015;Calao, Moreno-León, Correa, & Robles, 2015;Dorling & White, 2015). Otras Instituciones y profesores han usado entornos alternativos a Scratch porque coinciden en los beneficios que aportan en los estudiantes (Cheng, Fu, & Chen, 2016;Worrell, Brand, & Repenning, 2015;Jenkins, 2015;Berland & Wilensky, 2015;Han, Kim, & Wohn, 2015;Sarmento, Reis, Zaramella, Almeida, & Tacla, 2015) e inclusive han propuesto contenidos temáticos o cursos para niños de 11-12 años (Duncan & Bell, 2015;Hui-Chi, Chiu-Fan, Cheng-Chih, & Yu-Tzu, 2015;Yadav, Mayfield, Zhou, Hambrusch, & Korb, 2014) y la organización de torneos abiertos para niños de hasta 14 años indica una confianza global por parte de las Instituciones educativas (UK Bebras Computational Thinking Challenge, 2015;Talent Search, 2015). El pensamiento computacional en estudios preuniversitarios es una herramienta que, en combinación con otras metodologías, los maestros tienen para crear escenarios y actividades de aprendizaje que son efectivas para ayudar a los jóvenes a resolver problemas mediante el uso de la tecnología con que viven a diario (García-Peñalvo F. J., 2018; Llorens-Largo, García-Peñalvo, Molero-Prieto, & Vendrell-Vidal, 2017).…”
Section: Preuniversitariounclassified